A systematic literature review of creativity thinking in primary school: a systematic review of research trends and frameworks - Ludfi Arya Wardana; Wahyu Sukartiningsih; Neni Mariana (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
Creative thinking is a skill that students must have in the 21st Century. This study aims to identify research trends on creative thinking in primary schools, the types of qualitative research used, countries that frequently publish on creative thinking, journals with the highest SJRs publishing creative thinking, researchers who frequently research creative thinking in primary schools, what elements are frequently implemented in creative thinking in primary schools and creative thinking frameworks from 2013-2024. The review procedure included searching, screening, evaluating and synthesizing publications on creative thinking in primary schools. There were 50 articles published in Scopus indexed popular journals. The analysis reveals prominent journals such as Thinking Skills and Creativity and British Journal of Education Technology, and identifies key researchers contributing to the field. The study highlights the frequent use of qualitative methods such as descriptive qualitative, case studies, phenomenology, grounded theory, and ethnography, across various countries including Slovenia, Malaysia, and the UK. What types of qualitative methods are used in applying creative thinking skills in elementary schools, namely descriptive qualitative, case studies, phenomenology, grounded theory, and ethnography.